Assessing the Impact of Arctic Melting in the Predominantly Multilateral World System - Sakib, S M Nazmuz (Asian Pacific Journal of Environment and Cancer, 2022)
According to the global average, the Arctic is melting twice as fast as the rest of the world. Increasing temperatures in the polar regions area are in line with greenhouse gas emissions, implying that anthropogenic forcing is causing Arctic climate change. Arctic sea ice is quickly receding, resulting in a shifting geopolitical environment, among other things. Russia, Canada, the United States, Denmark, Norway, Iceland, and Finland–are the most important players which are called as Arctic eight, also China has made major attempts to establish itself as an Arctic participant. Aside from political maneuvering for power, the Arctic is a major source of concern for the whole world. Changes in the Arctic climate have worldwide consequences since its natural climate systems govern global climate systems and chill the globe. It is expected that by the end of the century there will be no ice in the summers in Arctic. The possibility of ice-free Arctic seas has sparked study on the use of the Northern Sea Route and the Northwest Passage as international trade routes, according to a growing scientific agreement. If these Arctic rivers are made commercially viable, transit times may be cut in half, encouraging increasing bilateral trade between major western European trading ports and northeast Asian powers like China, South Korea, and Japan. Proclamations of a rapidly changing foreign trade environment, on the other hand, are unfounded and exaggerated. A catastrophic lack of resources, a Russian dominance on transit costs, exorbitant insurance premiums, and extreme data scarcity are just a few of the many hurdles to shipping across these Arctic seas. This notion that worldwide trade would soon migrate northwards is one of the Arctic myths that is propagated by the mainstream media, and it serves to obscure the actual complexity of the Arctic melting. Mass media frequently promotes stories of a looming global war over unclaimed Arctic hydrocarbon resources, indicating a link between melting ice and sovereignty issues. Massive oil and natural gas deposits exist beneath the Arctic Circle. According to the US Geological Survey, the Arctic holds roughly 13% of the world’s undiscovered oil reserves and nearly 30% of the world’s unknown natural gas reserves. The melting ice covers a variety of responses from the fossil fuel businesses in Arctic nations. Most importantly, as ties with the West worsen, Russia intends to increase its offshore drilling and exploration, supported by investments from an enthusiastic China. Other countries, such as Canada and Norway, who rely heavily on oil and gas exports, play with sustainable investments in other areas while their fossil fuel businesses continue to operate largely unimpeded by calls for environmental sustainability. To ignore such nuances is to miss out on a thorough grasp of the Arctic’s geopolitical potential and challenges.